PENGARUH RASIO LIKUDITAS, PERTUMBUHAN PENJUALAN DAN AKTIVITAS TERHADAP PROFITABILITAS - Hermin Sirait; Vivi Novianti; Rohani Lestari (ITB AAS Indonesia Surakarta, 2024)
This study was proposed to determine how much influence the liquidity ratio, sales growth and activity have on profitability in automotive sub-sector companies. This study uses secondary data, the financial data of automotive companies listed on the IDX for the period 2018 – 2022. The sample technique uses purposive sampling and the analytical tool technique uses simple linear and multiple linear regression. The results of this study indicate that liquidity ratio, sales growth ratio and activity ratio partially have effect on profit. The Liquidity ratio, sales growth ratio and activity ratio simultaneously also have effect on profit growth. The variables show effect on profit, with an Adjusted R2 value of 0.0596 (59.6%), which means that the variables, Current Ratio, sales growth and Inventory Turnover, have effect on profit 59.6 % while the remaining 40.4% is explained by other variables beyond this. Partially the quality of the liquidity ratio, sales growth and activities have effect on profit.